Detecting Volemic, Cardiac, and Autonomic Responses From Hypervolemia to Normovolemia via Non-Invasive ClearSight Hemodynamic Monitoring During Hemodialysis: An Observational Investigation - Chih-Jun Lai (Frontiers in Physiology, 2022)
Background: Unstable hemodynamics are not uncommon during hemodialysis (HD), which involves a rapid volume depletion, taking the patient from hypervolemia toward euvolemia. Since uremic patients commonly have cardiovascular comorbidities, hemodynamic changes during HD may reflect interactions among the volemic, cardiac, and autonomic responses to gradual volume depletion during ultrafiltration. Accurate identification of inappropriate responses helps with precisely managing intradialytic hypotension. Recently, the non-invasive ClearSight was reported to be able to detect causes of intraoperative hypotension. In this prospective observational study, we aimed to determine whether ClearSight could be used to detect patterns in stroke volemic, cardiac, and vasoreactive responses during HD.Methods: ClearSight was used to monitor chronic stable patients receiving maintenance HD. Data of mean arterial blood pressure (MAP), heart rate (HR), stroke volume index (SVI), cardiac index (CI), and calculated systemic vascular resistance index (SVRI) were obtained and analyzed to examine patterns in volemic, cardiac, and vasoreactive changes from T0 (before HD) until T8 in 30-min intervals (total 4 h).Results: A total of 56 patients with a mean age of 60.5 years were recruited, of which 40 of them were men. The average ultrafiltration volume at T8 was 2.1 ± 0.8 L. The changes in MAP and HR from T0 to T8 were non-significant. SVI at T7 was significantly lower than that at T1, T2, and T3. CI at T4 to T8 was significantly lower than that at T0. SVRI was significantly higher at T3 to T8 than at T0. Pearson’s correlation coefficients between SVI and CI and between SVRI and MAP were positive at all time points. The correlation coefficients between SVRI and SVI and between CI and SVRI were significant and negative for all time points.Conclusion: ClearSight was able to detect patterns in hypervolemia during HD and was well tolerated for 4 h. CI decreased significantly after T4, with slightly decreased SVI. Ultrafiltration volume was not correlated with changes in SVI or CI. The vascular tone increased significantly, and this counteracted the reduced cardiac output after T4. With simultaneous monitoring on SVI, CI, and SVRI during HD, therefore, hypotension could be detected and managed by reducing the filtration rate or administering inotrope or vasopressors.Trial Registration:clinicaltrials.gov, ID: NCT03901794.